2005
DOI: 10.1074/jbc.m501241200
|View full text |Cite
|
Sign up to set email alerts
|

Asparagine Deamidation Perturbs Antigen Presentation on Class II Major Histocompatibility Complex Molecules

Abstract: Post-translational protein modifications can be recognized by B and T lymphocytes and can potentially make "self"-proteins appear foreign to the immune system. Such modifications may directly affect major histocompatibility complex-restricted T cell recognition of processed peptides or may perturb the processing events that generate such peptides. Using the tetanus toxin C fragment protein as a test case, we show that spontaneous deamidation of asparagine residues interferes with processing by the enzyme aspar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(58 citation statements)
references
References 36 publications
0
58
0
Order By: Relevance
“…7,23,42 Deamidation of long-lived self-proteins may qualitatively or quantitatively affect the spectrum of self-displayed peptides to T cells and thus contributing to exacerbation of auto immune diseases. 43,44 It has also been suggested that in vivo deamidation of proteins could serve as a molecular timer of many important biological events, such as aging. 5,[45][46][47] Few studies have attempted to investigate the consequences of deamidation by directly investigating the altered properties or by mutating the deamidated site.…”
Section: Residual Activity and Deamidation Status In Heat Cycled Mutcmentioning
confidence: 99%
“…7,23,42 Deamidation of long-lived self-proteins may qualitatively or quantitatively affect the spectrum of self-displayed peptides to T cells and thus contributing to exacerbation of auto immune diseases. 43,44 It has also been suggested that in vivo deamidation of proteins could serve as a molecular timer of many important biological events, such as aging. 5,[45][46][47] Few studies have attempted to investigate the consequences of deamidation by directly investigating the altered properties or by mutating the deamidated site.…”
Section: Residual Activity and Deamidation Status In Heat Cycled Mutcmentioning
confidence: 99%
“…However, the deamidation that occurs in vitro during the isolation of proteins and subsequent storage can adversely affect the biological properties of the protein. Effects on epitope structure, antigen processing, and antigen presentation represent negative outcomes that are particularly relevant to vaccine development (15,16). The rate of deamidation of any given Asn or Gln residue depends on a number of parameters, including primary structure (neighboring amino acids), pH, temperature, and ionic strength.…”
mentioning
confidence: 99%
“…Alternatively, changes in the amino acid sequence of rPA due to deamidation might affect antigen processing by altering critical target sites for the proteases involved in antigen processing. Such a phenomenon has been described for tetanus toxin fragment C (12). Those authors showed that deamidation of Asn residues interfered with processing of the protein, which affected generation of a T-cell response as assessed using an in vitro assay.…”
Section: Discussionmentioning
confidence: 72%
“…Deamidation of Asn occurs in vivo on a time scale ranging from a few seconds to centuries, depending on the local environment (10). In theory, deamidation might adversely affect the interaction of rPA with the aluminum adjuvant of the vaccine, might alter the epitope structure of the antigen, and/or might affect the ability of the protein to elicit T-cell help for antibody production which, in turn, might affect the vaccine immunogenicity (11)(12)(13)(14)(15).Earlier studies have demonstrated that certain Asn residues of rPA deamidate during the purification process and upon storage (8,16,17). Previously, we generated a mutant form of rPA in which the six Asn residues that are the most prone to deamidation were changed to Asp residues (six-Asp mutant rPA).…”
mentioning
confidence: 99%
See 1 more Smart Citation